2004
DOI: 10.1017/s001216220400101x
|View full text |Cite
|
Sign up to set email alerts
|

Non-verbal development of children with deafness with and without cochlear implants

Abstract: Deprivation of sensory input affects neurological development. Our objective was to explore clinically the role of hearing in development of sensorimotor integration and non-verbal cognition. The study involved 54 children (15 males, 839 females; 5 to 9 years old) with severe or profound bilateral prelocutive deafness but without neurological or cognitive impairment. Of these, 25 had received an early cochlear implant (CIm). Patients were compared with 40 children with normal hearing. All were given a battery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 25 publications
4
43
0
2
Order By: Relevance
“…The finding that children with hearing impairment have greatly increased levels of motor incoordination across all ZNA subscales compared with hearing children agrees closely with most earlier findings, 5,7,8,13 and is for the first time, to our knowledge, based upon a representative sample.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The finding that children with hearing impairment have greatly increased levels of motor incoordination across all ZNA subscales compared with hearing children agrees closely with most earlier findings, 5,7,8,13 and is for the first time, to our knowledge, based upon a representative sample.…”
Section: Discussionsupporting
confidence: 90%
“…Impairments of vestibular functioning after implantation are argued as damage caused by surgical trauma or indirect electrical stimulation; others state only temporary dysfunctions or describe long-term positive benefits on motor performance. 5,7,8 While in one study motor deficits in children with hearing impairment were not related to age, 5 Kammerer 9 found that neurological soft signs (mainly associated movements) were not less pronounced in older children. Others showed a negative correlation between fine motor skills and age.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…• Differences have been consistently documented in children with hearing loss in the areas of balance, complex motor sequencing, sensory, and vestibular processing (Cushing, Papsin, Rutka, James, & Gordon, 2008;Schlumberger, Narbona, & Manrique, 2004;Suarez et al, 2007). …”
Section: The Problemmentioning
confidence: 99%
“…The children's communication mode was not reported, but the time period of the study suggests that the children were probably using analog hearing aids and lip reading to aid their oral language development. Another study found that deaf children who used cochlear implants exhibited a delay in the development of motor sequencing and balance compared to hearing children (Schlumberger, Narbona, & Manrique, 2004). The authors also compared performance of a group of deaf children who used hearing aids, and they performed worse than both the hearing children and the deaf children who used cochlear implants.…”
Section: Discussionmentioning
confidence: 99%